Exciting High-Order Plasmon Mode Using Metal-Insulator-Metal Bowtie Nanoantenna - Xiaoxin Zhang; Rulin Guan; Qingxiu Ding; Chen Wang; Yaqiong Li; Dengchao Huang; Qigong Chen; Zheng Yang (Nanomaterials, 2025)
Noble metal nanostructures have garnered significant attention for their exceptional optical properties, particularly Localized Surface Plasmon Resonance (LSPR), which enables pronounced near-field electromagnetic enhancements. Among these, bowtie nanoantennas (BNAs) are distinguished by their intense plasmonic coupling within nanogap regions, making them highly effective for applications such as surface-enhanced Raman scattering (SERS). However, the practical utility of conventional BNAs is often hindered by small hotspot areas and significant scattering losses at their peak near-field enhancement wavelengths. To overcome these limitations, we have designed a novel notch metal-insulator-metal bowtie nanoantenna (NMIM-BNA) structure. This innovative design integrates dielectric materials with Ag-BNA nanostructures and strategically positions arrays of silver (Ag) nanorods within the central nanogap. By coupling the larger NMIM-BNA framework with these smaller Ag nanorod arrays, higher-order plasmon modes (often referred to as dark modes) are effectively excited. Consequently, the NMIM-BNA exhibits substantial electric field enhancement, particularly at the Fano dip wavelength, arising from the efficient coupling of these higher-order plasmon modes with dipole plasmon modes. Compared to conventional Ag-BNA nanoantennas, our NMIM-BNA provides a significantly larger hotspot region and an enhanced near-field amplification factor, underscoring its strong potential for advanced SERS applications.